2016
DOI: 10.1017/s1751731115001457
|View full text |Cite
|
Sign up to set email alerts
|

Lameness detection in dairy cattle: single predictor v. multivariate analysis of image-based posture processing and behaviour and performance sensing

Abstract: The objective of this study was to evaluate if a multi-sensor system (milk, activity, body posture) was a better classifier for lameness than the single-sensor-based detection models. Between September 2013 and August 2014, 3629 cow observations were collected on a commercial dairy farm in Belgium. Human locomotion scoring was used as reference for the model development and evaluation. Cow behaviour and performance was measured with existing sensors that were already present at the farm. A prototype of three-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…A further opportunity to improve the detection accuracy of an integrated automatic assessment system would be to integrate not only sensor data, but also non-sensor information, such as herd data [26,105]. For instance, information on days in milk, parity and previous incidence of a specific welfare issue could all be helpful to identify individuals that would be more at risk to suffer from certain welfare issues (e.g., [17,18]).…”
Section: Opportunities and Challenges For Integrated Automatic Assessmentioning
confidence: 99%
See 1 more Smart Citation
“…A further opportunity to improve the detection accuracy of an integrated automatic assessment system would be to integrate not only sensor data, but also non-sensor information, such as herd data [26,105]. For instance, information on days in milk, parity and previous incidence of a specific welfare issue could all be helpful to identify individuals that would be more at risk to suffer from certain welfare issues (e.g., [17,18]).…”
Section: Opportunities and Challenges For Integrated Automatic Assessmentioning
confidence: 99%
“…For instance, in the assessment of heat stress both environment-based indicators, such as ambient temperature, and animal-based indicators, such as respiratory rate, could be measured (e.g., [15,16]). While studies often focus on testing the performance of one automatic detection method, several studies have found that integrating data from different detection methods improves the detection performance (e.g., [17,18]; reviewed by [19]) and commercial systems that integrate several parameters, such as RumiWatch (Itin + Hoch GmbH, Liestal, Switzerland [20]) and Cow Manager SensOor (Agis Automatisering BV, Harmelen, the Netherlands [21]), have been suggested to outperform systems with less or one parameter [22,23]. However, there is still a need to integrate data from many systems to into one system that would be able to make an overall assessment of the welfare of an animal (e.g., [24,25]).…”
Section: Introductionmentioning
confidence: 99%
“…One that is based on physical variables and gait movements detected lameness and even the limb that causes it (Rajkondawar et al ., 2006; Liu et al ., 2009). Another lameness detection sensor based on the posture and back curvature of walking cows (Van Hertem et al ., 2016, 2018) indicated lameness before its visual appearance. Both products were put on the market, but did not meet expectations and are not yet widely used.…”
Section: Sensors For Healthmentioning
confidence: 99%
“…Frequent monitoring of animals’ body condition in quantitative terms is helpful in order to allow for early recognition of health anomalies and consequently decrease the amount of complications related to infertility, lameness, or other animal diseases [ 1 , 2 , 3 , 4 ]. With reference to young calves, the first months of life are critical, since animals’ growth may be affected by the appearance of several diseases or other stress factors, such as dehorning [ 5 ].…”
Section: Introductionmentioning
confidence: 99%